2023
DOI: 10.1097/md.0000000000034402
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of hypertension among middle-aged and elderly adults in Anhui Province

Yujia Zhai,
Can Cui,
Tianyun Yu
et al.

Abstract: To understand and analyze the prevalence and treatment of hypertension among residents aged 45 years and older in northern and southern Anhui Province to provide an opportunity to improve awareness, taking into account and standardizing hypertension management. Using a stratified cluster random sampling method, Anhui Province was divided into northern and southern Anhui regions using the Yangtze River as the boundary. The prevalence rate, awareness rate, treatment rate, control rate, related risk factors and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A population-based cohort study in Sweden found that people with hypertension had higher nervousness scores compared to normal people ( 44 ). To our knowledge, older adults with hypertension are inherently considered a vulnerable population, and the presence of physical complications from hypertension and concerns about future life can exacerbate their feelings of nervousness ( 5 ), which may eventually lead to depression, anxiety, and other psychological health issues ( 6 ). In addition, both exploratory factor analysis studies and network analysis studies have discovered that nervousness is an important transdiagnostic symptom associated not only with anxiety but also with depression ( 19 , 42 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A population-based cohort study in Sweden found that people with hypertension had higher nervousness scores compared to normal people ( 44 ). To our knowledge, older adults with hypertension are inherently considered a vulnerable population, and the presence of physical complications from hypertension and concerns about future life can exacerbate their feelings of nervousness ( 5 ), which may eventually lead to depression, anxiety, and other psychological health issues ( 6 ). In addition, both exploratory factor analysis studies and network analysis studies have discovered that nervousness is an important transdiagnostic symptom associated not only with anxiety but also with depression ( 19 , 42 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with hypertension inherently have a more delicate constitution compared to their healthier counterparts. If they fail to maintain regular antihypertensive treatment, they are more prone to severe complications such as coronary heart disease, heart failure, cerebral infarction, or cerebral hemorrhage ( 5 ). The physical complications and uncertainty about future health could potentially impose substantial psychological stress on older adults afflicted with hypertension, leading them to grapple with psychological afflictions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation